FORCE platform overcomes barriers of oligonucleotide delivery to muscle and corrects myotonic dystrophy features in preclinical models - Timothy Weeden; Tyler Picariello; Brendan Quinn; Sean Spring; Pei-Yi Shen; Qifeng Qiu; Benjamin F. Vieira; Lydia Schlaefke; Ryan J. Russo; Ya-An Chang; Jin Cui; Monica Yao; et al. (Communications Medicine)
Abstract Background We developed the FORCETM platform to overcome limitations of oligonucleotide delivery to muscle and enable their applicability to neuromuscular disorders. The platform consists of an antigen-binding fragment, highly specific for the human transferrin receptor 1 (TfR1), conjugated to an oligonucleotide via a cleavable valine-citrulline linker. Myotonic dystrophy type 1 (DM1) is a neuromuscular disorder caused by expanded CUG triplets in the DMPK RNA, which sequester splicing proteins in the nucleus, lead to spliceopathy, and drive disease progression. Methods Multiple surrogate conjugates were generated to characterize the FORCE platform. DYNE-101 is the conjugate designed to target DMPK and correct spliceopathy for the treatment of DM1. HSALR and TfR1 hu/mu ;DMSXL Tg/Tg mice were used as models of myotonic dystrophy, the latter expresses human TfR1 and a human DMPK RNA with >1,000 CUG repeats. Cynomolgus monkeys were used to determine translatability of DYNE-101 pharmacology to higher species. Results In HSALR mice, a surrogate FORCE conjugate achieves durable correction of spliceopathy and improves myotonia to a greater extent than unconjugated ASO. In patient-derived myoblasts, DYNE-101 reduces DMPK RNA and nuclear foci, consequently improving spliceopathy. In TfR1 hu/mu ;DMSXL Tg/Tg mice, DYNE-101 reduces mutant DMPK RNA in muscle, thereby correcting splicing. Reduction of DMPK foci in cardiomyocyte nuclei accompanies these effects. Low monthly dosing of DYNE-101 in TfR1 hu/mu ;DMSXL WT/Tg mice or cynomolgus monkeys leads to a profound reduction of DMPK expression in muscle. Conclusions These data validate FORCE as a drug delivery platform and support the notion that DM1 may be treatable with low and infrequent dosing of DYNE-101.